Green Tea Extract Protects Endothelial Progenitor Cells from Oxidative Damage Through Reduction of Intracellular Reactive Oxygen Species Activity - Widowati, Wahyu; Widyanto, Rahma Micho; Laksmitawati, Dian Ratih; Husin, Winsa; Ratnawati, Hana; Bachtiar, Indra (Proceeding ICBB (The International Conference on Bioscience and Biotechnology), 2011)
A number studies have examined that tea consumption decreases cardiovascular risk, but the mechanisms remain undefined. Endothelial dysfunction has been correlated with coronary artery disease and circulating endothelial progenitor cells (EPCs) is contributed of this repair process. Endothelial dysfunction is associated with increased oxidative stress and may be reverse by antioxidant. Green tea is known as free radical scavenger which has a powerful antioxidant action. The aim of this study is to investigate whether green tea extract (GTE) can protect EPCs from oxidative stress through antioxidant protective mechanism. Total mononuclear cells (MNCs) were isolated from peripheral blood by Ficoll density gradient centrifugation. The cells were then plated on fibronectin-coated culture dishes. After being cultured for 7 d, EPCs were characterized as adherent cells double positive for DiLDL-uptake and lectin binding. Further characterizations were done by demonstrating the expression of CD34/45, CD133, and KDR. EPCs were then induced for oxidative stress using various concentrations of H2O2 (50, 100, 200 µM), and incubated with or without GTE (25 mg/L) and result showed that GTE ameliorated the cell viability of H202-induced EPC at concentration 50, 100, 200 µM for about 28.72 ± 10.5%, 34.55 ± 7.64%, and 27.04 ± 3.42%, respectively, higher than that control. The level of intracellular reactive oxygen species (ROS) was quantified by fluorescence with 2’,7’- dichlorofluorescein diacetate (DCFH-DA) using flow cytometry and showed that GTE decreased intracellular ROS level of H202- induced EPC at concentration 50, 100, 200 µM for about 84.24 ± 8.59 %, 92.27 ± 1.08 %, and 93.72 ± 0.36%, respectively, compare to that control. The result showed that GTE may ameliorate cell viability by decreasing accumulation of intracellular ROS in H202-induced EPCs.